PENGARUH INTEGRITAS, AKUNTABILITAS, KEAHLIAN, PROFESIONALISME, MOTIVASI AUDITOR TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS DALAM PEMERIKSAAN LAPORAN KEUANGAN (Studi Empiris Pada Kantor Akuntan Publik di Sumatera) - Solihat, Putri Ayu; Indrawati, Novita; Hariadi, Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to determine the effect of integrity, accountability, expertise,professionalism, auditor motivation on material level considerations in the examinationof financial statements. This research was conducted at a public accounting firm inSumatra. The population in the study were all auditors working in KAP (PublicAccounting Firm) in Sumatra as many as 58 KAP with a total auditor of 250 auditors.The Sampling method in this study uses the census method. The data analysis methodused in this study is multiple linear regression analysis using software product andservice solution (SPSS) version 19.0. The results of the study show that integrity,accountability, expertise, professionalism and auditor motivation have an influence onthe consideration of materiality levels in examining financial statements.Keywords : Integrity, Accountability, Expertise, Professionalism, Auditor Motivation,Consideration of Materiality Level